Altered Signaling and Cell Cycle Regulation in Embryonal Stem Cells with a Disruption of the Gene for Phosphoinositide 3-Kinase Regulatory Subunit p85α() - Hallmann, Daniel (2002)
The p85α regulatory subunit of class I(A) phosphoinositide 3-kinases (PI3K) is derived from the Pik3r1 gene, which also yields alternatively spliced variants p50α and p55α. It has been proposed that excess monomeric p85 competes with functional PI3K p85-p110 heterodimers. We examined embryonic stem (ES) cells with heterozygous and homozygous disruptions in the Pik3r gene and found that wild type ES cells express virtually no monomeric p85α. Although, IGF-1-stimulated PI3K activity associated with insulin receptor substrates was unaltered in all cell lines, p85α-null ES cells showed diminished protein kinase B activation despite increased PI3K activity associated with the p85β subunit. Furthermore, p85α-null cells demonstrated growth retardation, increased frequency of apoptosis, and altered cell cycle regulation with a G(0)/G(1) cell cycle arrest and up-regulation of p27(KIP), whereas signaling through CREB and MAPK was enhanced. These phenotypes were reversed by re-expression of p85α via adenoviral gene transfer. Surprisingly, all ES cell lines could be differentiated into adipocytes. In these differentiated ES cells, however, compensatory p85β signaling was lost in p85α-null cells while increased signaling by CREB and MAPK was still observed. Thus, loss of p85α in ES cells induced alterations in IGF-1 signaling and regulation of apoptosis and cell cycle but no defects in differentiation. However, differentiated ES cells partially lost their ability for compensatory signaling at the level of PI3K, which may explain some of the defects observed in mice with homozygous deletion of the Pik3r1 gene.